Using social media to fundraise in a higher education context - Smart, Chris (2012)
Today accessing social media is part of the daily routine for millions of people and facilitates billions of conversations every year, often between individuals who have and never will meet in real life. For many it is a way to share their news, thoughts and experiences with friends and family and for many organisations it is a way to get involved in those conversations. This report investigates how UK higher education institutes (HEIs) currently use social media to facilitate fundraising programmes. Philanthropy is an increasingly important source of funding for UK HEIs and social media has the potential to help organisations to reach a larger population than more traditional communication channels. Information was collected using a detailed survey completed by development professionals within UK HEIs and social media consultants. The report considers what lessons can be learned from US HEIs, charities and businesses in their use of social media and makes a series of recommendations for HEIs and The University of Nottingham to consider.